Analysis of the mechanism of Zangjiangzhi capsule in the treatment of hyperlipidemia based on its ingredients identified by UHPLC-Q-Exactive-Orbitrap-MS - Changting He; Yuling Zhao; Yongchun Huang; Yudong Su; Shoude Zhang (Journal of Traditional Chinese Medical Sciences)
Objective: To explore the mechanism of action of Zangjiangzhi capsule (ZJZC) in treating hyperlipidemia (HLP). Methods: The components of ZJZC were analyzed and identified using ultra-high performance liquid chromatography with Q-Exactive Orbitrap tandem mass spectrometry (UHPLC-Q-Exactive-Orbitrap-MS/MS). Network pharmacology analysis was used to explore the mechanism of action of ZJZC in HLP treatment. The SwissTargetPrediction database was used to predict compound targets, and GeneCards, DisGeNet, OMIM, and DRUGBANK databases were used to identify HLP-related targets. Protein–protein interaction diagrams were constructed using the STRING database. The targets were subjected to gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The “herb-ingredient-target” network was visualized using Cytoscape. Preliminary validation was performed using molecular docking and enzyme-linked immunosorbent assay. Results: Ninety compounds were identified in ZJZC, including 34 flavonoids, 12 phenols, 10 terpenoids, 10 alkaloids, 8 organic acids, 8 anthraquinones, and 9 other compounds. In total, 904 targets were identified for these compounds. Among them, 158 targets intersected with the HLP target network. Network pharmacology analysis showed that MAPK1, PPAR-α, RXRA, HSP90AA1, PIK3R1, AKT1, PIK3CA, IL6, TNF, and ESR1 are the key targets of action. KEGG enrichment analysis identified 164 pathways. Among these, the AGE-RAGE signaling pathway in diabetic complications, lipid and atherosclerosis pathways, regulation of lipids in adipocytes, and insulin resistance are related to HLP. Molecular docking showed good affinity between the key targets and ingredients. Further, ZJZC treatment in mice resulted in lower expression of MAPK1 protein and increased expression of PPAR-α protein, which have been shown to be strongly associated with HLP. Conclusions: This study showed that ZJZC contains various active ingredients and can modulate multiple targets and pathways associated with HLP, providing evidence at the molecular level for its clinical application in the treatment of HLP.